Brightness of Blue/Violet Luminescent Nano-Crystalline AZO and IZO Thin Films with Effect of Layer Number: For High Optical Performance*Support by the ERA.Net Rus STP-212 Project. (May 2016) - Korallı, Panagiota; Varol, Songül Fıat; Kompitsas, Michael; Girtan, Mihaela
Abstract : From different reports, it is realized that there is a need to consider all sides of aluminum-doped zinc oxide (AZO) and indium-doped zinc oxide (IZO) thin films with their optical, luminescence and surface properties including usage areas. We establish an assessment to carry out further information to summarize AZO and IZO nanocrystalline films with impact of the layer number.